Japan's grand strategic shift from Yoshida to Koizumi: reflection on Japan's strategic focus in the 21st Century. - Tang , Siew Man (Universiti Kebangsaan Malaysia, 2007)
Sila rujuk teks penuh/ Please refer to full text